2010
DOI: 10.1021/jf100758x
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate Composition of High-Fructose Corn Syrups (HFCS) Used for Bee Feeding: Effect on Honey Composition

Abstract: In this study, the carbohydrate composition of high-fructose corn syrups (HFCS) from commercial manufacturers as well as from beekeepers was characterized by GC-MS. Sucrose syrups (SS) were also included in this work for comparison. Fructosyl-fructoses and some unknown carbohydrates, which could correspond to fructosyl-glucoses, have been detected in HFCS for the first time, whereas SS were mainly characterized by the high contents of sucrose. Hydroxymethylfurfural (HMF) content of samples supplied by beekeepe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(40 citation statements)
references
References 16 publications
2
36
0
1
Order By: Relevance
“…This might be resulted from high fructose content of the HFCS-85 compared to the other sugars (Table 1). This result was compatible with the result of Ruiz-Matute et al [7] who used HFCS-42, HFCS-55, HFCS-75, HFCS+SS and SS sugars for feeding the honey bees. In our study, the honeys taken from the 20 and 100 L/colony of HFCS-85 evaluated as fraudulent due to the fact that they showed significant deviations from standard values [2,30] .…”
Section: Discussonsupporting
confidence: 82%
See 4 more Smart Citations
“…This might be resulted from high fructose content of the HFCS-85 compared to the other sugars (Table 1). This result was compatible with the result of Ruiz-Matute et al [7] who used HFCS-42, HFCS-55, HFCS-75, HFCS+SS and SS sugars for feeding the honey bees. In our study, the honeys taken from the 20 and 100 L/colony of HFCS-85 evaluated as fraudulent due to the fact that they showed significant deviations from standard values [2,30] .…”
Section: Discussonsupporting
confidence: 82%
“…PBH had no sucrose. Ozcan et al [33] and Ruiz-Matute et al [7] also found no sucrose in control honey. The source of sucrose in the pure honey, where sucrose was not used as a supplemental food in this group, is nectar [5,[32][33][34] .…”
Section: Discussonmentioning
confidence: 99%
See 3 more Smart Citations